Effects of fertilizer reduction coupled with straw returning on soil fertility, wheat root endophytic bacteria, and the occurrence of wheat crown rot - Wang, Yajiao; Wu, Yuxing; Cao, Caiyun; Han, Sen; Zhao, Weisong; Li, Qiusheng; Liu, Xuetong; Kong, Lingxiao (Frontiers in Microbiology, 2023)
Excessive fertilization is associated with nutrient loss, soil compaction and weak plant resistance. Straw returning can increase soil fertility with a consequent reduction in fertilizer, but the effects of fertilizer reduction coupled with straw returning on crop endophytic microbes and crop disease are poorly understood. Therefore, we investigated the responses of soil fertility, diversity and function of root endophytic bacteria, and the occurrence of wheat crown rot to the fertilizer application (no, moderate and excessive fertilizer) coupled with or without straw returning after 7 years treatments. The results showed that after excessive fertilization, the wheat crown rot became severe, registering a disease index of 23. Compared with excessive fertilization, moderate fertilization coupled with straw returning significantly reduced the incidence of wheat crown rot, the disease index was reduced by 38.50% , the richness and diversity of endophytic bacteria were increased by 61.20% and 11.93% respectively, but the soil fertility was not significantly affected. In addition, moderate fertilization coupled with straw returning changed the community structure of endophytic bacteria, and increased the the relative abundance of carbohydrate metabolism and nitrogen fixation related genes by 4.72% and 9.32% respectively. Our results indicated that fertilizer reduction coupled with straw returning reduced the occurrence of wheat crown rot, increased the diversity of endophytic bacteria and changed the community structure and function of endophytic bacteria, which will provide a better understanding about the interaction of fertilization coupled with straw returning -endophytic bacteria – whet crown rot and provide a theoretical basis for sustainable wheat production.